A Semiotic Analysis of Social Critique in the “Mari Membaca” Music Video by Mesin Tempur, Based on Roland Barthes’s Theory - Hidayatullah Rizkyka Hartadhi, Syahiid; Syam Maella, Nur'annafi Farni Syam Maella; Ahmadi, Ahmadi; Nurchaerani, Meiyanti (UIBU, 2025)
This qualitative-descriptive study analyzes the social critique represented in the music video “Mari Membaca” by the band Mesin Tempur. The research background lies in the role of music videos as an effective medium for conveying profound messages and the urgency of literacy issues in Indonesia. Using Roland Barthes’s semiotic framework, this study deconstructs how social critique is constructed through intertwined visual and linguistic signs. Primary data were collected through direct observation of the music video to identify denotative signs, followed by analysis through Barthes’s three levels of meaning: denotation (literal meaning), connotation (implied meaning), and myth (ideological meaning). The findings reveal that the video systematically constructs a myth of literacy as an act of resistance. Through a semiotic contradiction between the aggressive, anti-establishment connotations of the grindcore/metal genre and the positive, constructive message of “let’s read”, the video redefines reading as a form of rebellion against ignorance. The study also demonstrates how semiotic analysis can reveal ideological constructions in music video culture. In conclusion, the study finds that “Mari Membaca” redefines literacy as a symbolic act of resistance, transforming it from an academic issue into a cultural movement that calls for public awareness and action.